Language Teaching Materials and Learner Motivation in Ma’arif Nahdlatul Ulama University Students - Endah Mitsalina (ETERNAL (English Teaching Journal), 2015)
Recently, the motivation of the student is a standout amongst the most imperative factors in Foreign Language Acquisition (FLA), in the meantime language teaching materials are having an essential impact and part in language learning and educating process. This exploration has target on how diverse materials stimulate motivation of students. Numerous factors which influence student's motivation towards teaching materials were seen, for example, enthusiasm for the  topic, level of difficulty, importance to existing learning, impression of helpfulness.